التّناص في روايات الطّاىر وطار - سفيان نايل (جامعة البليدة 2 كلية الآداب واللغات, 2018)
Summary: the intertextuality in the novels of Tahar Ouettar : - Intertextuality is modern technology that has deep roots in our critical Arab heritage: the text in its building structure is the result of the interaction of past and present texts, and because the comparative lesson aims to break the fabric of this new text structure. then the phenomenon of intertextuality in the novels of "Tahar Ouettar". - In this treatise, we present the discourse of harmony in terms of origin and development, until it is settled by the researcher Julia Kristeva.This study was applied to deconstruct the text of the Uttartian narrative, the result being that the literary text is a process of understanding and interacting with many previous texts and their evocation, and that intertextual texts constitute an important element of its composition. and method of composition. - Tahar Ouettar have inspired the Koran in many of his novels and characters and in his positions in many Qur'anic and religious stories in general.- Tahar Ouettar take the characters and historical facts that he calls into his visible Romanesque masks through contemporary man, and turn his writings into tales that reflect the present through the intense evocation of the past.- We concluded that the myth of important sources in Tahar Ouettar's novels, an effective way to expand the writer's imagination, helps to express social and political feelings and emotions and show outstanding problems of the new world. The quantity of this patrimony in its various types is varied in the writer's narratives between religious recruitment and historical, mythical and popular employment, the evocation and attachment of the past to the present.
Keywords: اللاز; ركاية عرس بغؿ; جدار برلين